Extracting Business Value from IT: A Sensemaking Perspective of Post-Adoptive Use - Hsieh, J. J. Po-An; Rai, Arun; Xu, Sean Xin (Management Science, 2011)
How can firms extract value from already-implemented information technologies (IT) that support the work processes of employees? One approach is to stimulate employees to engage in post-adoptive extended use, i.e., to learn and apply more of the available functions of the implemented technologies to support their work. Such learning behavior of extending functions in use is ingrained in a process by which users make sense of the technologies in the context of their work system. This study draws on sensemaking theory to develop a model to understand the antecedents, contingencies, and consequences of customer service employees' extended use of customer relationship management (CRM) technologies. The model is tested using multisource longitudinal data collected through a field study of one of the world's largest telecommunications service providers. Our results suggest that employees engage in post-adoptive sensemaking at two levels: technology and work system. We found that sensemaking at both of these levels impacts the extended use of CRM technologies. Employees' sensemaking at the technology level is influenced by employees' assessment of technology quality, whereas employees' sensemaking at the work system level is influenced by customers' assessment of service quality. Moreover, in the case of low technology quality and low service quality, specific mechanisms for employee feedback should be conceptualized and aligned at two levels: through employee participation at the technology level and through work system coordination at the work system level. Such alignment can mitigate the undesirable effect of low technology quality and low service quality, thereby facilitating extended use. Importantly, we found that extended use amplifies employees' service capacity, leading to better objective performance. Put together, our findings highlight the critical role of employees' sensemaking about the implemented technologies in promoting their extended use of IT and improving their work performance. This paper was accepted by Sandra Slaughter, information systems.